Kajian Penetapan Komoditi Pertanian Unggulan UMKM di Kota Batam - Dwi Kartikasari; Muhammad Zaenuddin (EKO-REGIONAL, 2010)
This paper concerns about commodity/products/business selection on the priority to develop for micro-small-medium enterprise in Batam municipality according to Analytical Hierarchy Process (AHP) method. The objectives aimed in the method are a) vocation creation, b) competitiveness improvement, and c) economic growth. The criteria taken for sub-district-level business selection are a) the number of businesses, b) market extent, c) materials availability, and d) local economic contribution. And the criteria given for municipality-level business selection are a) skilled labor availability, b) raw materials, c) financial capital, d) production utilities, e) technology, f) socio-culture, g) management, h) market, i) price, j) labor absorption, k) regional economic contribution. The respondents are stakeholders in sub-district level and municipality level. As a whole, the result of this research is that large frog (kangkung) is considered as superior commodity of small enterprise to develop in Batam. Keyworlds: agriculture commodity selection, AHP, small medium enterprise